User needs and design features of sanitation digital solutions in Kawempe division, Kampala Uganda: a user centered design approach - Mukasa, Comfort Hajra; Nankanja, Maureen; Walude, Mtwalib; Muzini, Maurice; Kagurusi, Patrick (Frontiers in Public Health, 2023)
Despite improvements in access to water and sanitation services globally, a significant population in Sub Saharan Africa has limited access to improved sanitation facilities. Furthermore, there is lack of a centralized digital platform for data exchange among stakeholders for sanitation services planning and provision in Uganda. A user centered design (UCD) approach was used to develop and pilot a one stop sanitation digital solutions (SaniDigS) center in Kawempe division, Kampala, Uganda. This involved three phases (1) understanding the sanitation status of the community which involved interviewing 1,844 household heads, (2) specifying the user needs of the proposed digital solution through stakeholder meetings and (3) Co designing of the innovations with potential users through stakeholder workshops. The quantitative data was visualized through the SaniDigS platform dashboard. The stakeholder meeting transcripts and notes were thematically analyzed to identify the user needs. The community user needs included an innovation that ensures confidentiality, is low cost and user friendly without internet connection. The service provider needed a sanitation digital solution that can market their sanitation products while, policy makers and planners needed comprehensive, real time data collection and sharing for trend analysis and informed decision making. The codesigned features of the SaniDigS informed by the user needs included: The SaniDigS Champion Application, SaniDigS platform dashboard, SaniDigS mobile application and the call center. The community in Kawempe showed need for subsidized sanitation products and we recommend further research to evaluate the effects of SaniDigS on planning, coordination, and access to sanitation services.